2014
DOI: 10.1126/science.1251456
|View full text |Cite|
|
Sign up to set email alerts
|

The STAT3-Binding Long Noncoding RNA lnc-DC Controls Human Dendritic Cell Differentiation

Abstract: Long noncoding RNAs (lncRNAs) play important roles in diverse biological processes; however, few have been identified that regulate immune cell differentiation and function. Here, we identified lnc-DC, which was exclusively expressed in human conventional dendritic cells (DCs). Knockdown of lnc-DC impaired DC differentiation from human monocytes in vitro and from mouse bone marrow cells in vivo and reduced capacity of DCs to stimulate T cell activation. lnc-DC mediated these effects by activating the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
856
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 966 publications
(873 citation statements)
references
References 37 publications
12
856
2
3
Order By: Relevance
“…The findings presented within this study are in line with previous reports suggesting that phosphorylation of STAT3 is regulated by a lncRNA, lnc-DC [5].…”
supporting
confidence: 82%
“…The findings presented within this study are in line with previous reports suggesting that phosphorylation of STAT3 is regulated by a lncRNA, lnc-DC [5].…”
supporting
confidence: 82%
“…SENCR knockdown decreased myocardin al 72) identified a dendritic cell-specific lncRNA termed lnc-DC playing a critical role in the differentiation of dendritic cells from human monocytes and mouse bone marrow, a cell type playing important roles in atherosclerosis 73) . Another study has shown that lncRNA APOA1-AS function as a negative transcriptional regulator and distinct histone methylation patterns modulator of APOA1 74) , a major component of HDL particles associated with reduced atherosclerosis 75) .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…Most microarray-based transcriptome analyses will for example miss a large proportion of long noncoding RNAs (lncRNAs), which are involved in almost all known cellular processes (10)(11)(12)(13)(14), and are important in cancer biology, as shown by the number of functional characterized lncRNAs involved in carcinogenesis (15). In EAC, only two lncRNAs have been reported (16,17), and no systematic approach identifying lncRNAs dysregulation at different stages of Barrett's disease and EAC development has been published so far.…”
Section: Introductionmentioning
confidence: 99%